The Impact of Anemia on Adolescent Girls in the Future - Mahfuzhah Deswita Puteri; Darmayanti Wulandatika; Siti Fatimah (CV Media Inti Teknologi, 2024)
This community service activity aims to increase teenagers' knowledge about anemia when teenagers are at risk of becoming pregnant and giving birth to stunted children in Banjarbaru City. This activity needs to be done because development during adolescence, greatly determines a person's ability to become an adult. Nutritional problems that occur during adolescence will increase vulnerability to disease in adulthood and risk giving birth to a generation with nutritional problems. For this reason, the community service team is expected to be able to carry out outreach activities to teenagers about anemia when teenagers are at risk of becoming pregnant and giving birth to stunted children. This activity uses the method of counseling and asking and answering teenagers' knowledge about anemia when teenagers are at risk of becoming pregnant and giving birth to stunted children. After carrying out this community service activity, the conclusion that can be drawn is that there is an increase in teenagers' knowledge about anemia when teenagers are at risk of becoming pregnant and giving birth to stunted children. The hope is that after gaining knowledge about anemia, teenagers can avoid it.